Export Performance of the Medium-Sized Industrial Business in the Urals - Andrey A. Maltsev (Экономика региона, 2020)
The development of non-resource exports is closely linked to the dynamics of medium-sized enterprises. This relationship comprises two strategic goals of Russian economic development stated in the national projects. Based on the data of the entities of the Ural region, the paper analyses the export potential of medium-sized industrial enterprises. In particular, the study examines the structure of the exporting business and clarify how the exporters estimate the state policy supporting non-resource exports. To collect and study data, I used various empirical tools. First, I compiled database of medium-sized industrial enterprises from seven Ural regions (Sverdlovsk, Chelyabinsk, Orenburg, and Kurgan Oblasts; Perm Krai; the Republic of Bashkortostan, and the Udmurt Republic). The sources for this database were SPARK-Interfax, open press, annual reports, and results of special queries. Second, the conducted survey of the Ural medium-sized industrial enterprises revealed that 15 % of them are exporters. Simultaneously, the contribution of medium-sized industrial enterprises to regional exports is consistent with the average Russian values; in two regions, this indicator is even higher than the average. The study revealed the difference in the estimations of the important state support measures between medium-sized exporters and non-exporters. While the established exporters choose the reduction of the tax burden as the most important measures, non-exporters prefer information support. However, the most demanded is to create general conditions for exports, ensure the stability of legal and administrative regulations, and implement proactive state policies supporting medium-sized enterprises. The research results can be used for creating and/or updating available regional support programmes for non-resource export of medium-sized enterprises. Further research in this field of non-resource exporters requires monitoring study and regular representative surveys.